Transduction of Craniofacial Motoneurons Following Intramuscular Injections of Canine Adenovirus Type-2 (CAV-2) in Rhesus Macaques - Bohlen, Martin O.; El-Nahal, Hala G.; Sommer, Marc A. (Frontiers in Neuroanatomy, 2019)
Reliable viral vector-mediated transgene expression in primate motoneurons would improve our ability to anatomically and physiologically interrogate motor systems. We therefore investigated the efficacy of replication defective, early region 1-deleted canine adenovirus type-2 (CAV-2) vectors for mediating transgene expression of fluorescent proteins into brainstem motoneurons following craniofacial intramuscular injections in four rhesus monkeys (Macaca mulatta). Vector injections were placed into surgically identified and isolated craniofacial muscles. After a 1- to 2-month survival time, animals were sacrificed and transgene expression was assessed with immunohistochemistry in the corresponding motoneuronal populations. We found that injections of CAV-2 into individual craniofacial muscles at doses in the range of ∼1010 to 1011 physical particles/muscle resulted in robust motoneuronal transduction and expression of immunohistochemically identified fluorescent proteins across multiple animals. By using different titers in separate muscles, with the resulting transduction patterns tracked via fluorophore expression and labeled motoneuron location, we established qualitative dose-response relationships in two animals. In one animal that received an atypically high titer (5.7 × 1011 total CAV-2 physical particles) distributed across numerous injection sites, no transduction was detected, likely due to a retaliatory immune response. We conclude that CAV-2 vectors show promise for genetic modification of primate motoneurons following craniofacial intramuscular injections. Our findings warrant focused attention toward the use of CAV-2 vectors to deliver opsins, DREADDs, and other molecular probes to improve genetics-based methods for primate research. Further work is required to optimize CAV-2 transduction parameters. CAV-2 vectors encoding proteins could provide a new, reliable route for modifying activity in targeted neuronal populations of the primate central nervous system.